Dual-Gated Low Operating Voltage Metal Oxide Thin-Film Transistor for Highly Sensitive and Fast-Response Pressure Sensing Application - Pandey U.; Pal N.; Acharya V.; Aich P.K.; Yadav A.K.; Pal B.N. (My University, 2025)
A solution-processed low operating voltage dual-gated metal oxide thin-film transistor (MOTFT) has been fabricated for pressure sensing applications. This device has been fabricated on a p-doped Si ( p+ -Si) using Li-alumina (Li-Al2O3) as a bottom gate dielectric and SnO2 thin film as a semiconductor channel. Besides, piezoelectric poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) thin film has been utilized as the top gate and dielectric on which external pressure has been applied. During bottom gate biasing, this TFT shows an n-channel behavior within 2-V operating voltage. Under such operation, the obtained value of threshold voltage ( V_ th) , carrier mobility ( μ ) , and ON/OFF ratio of this device is 0.12 V, 2.60 cm 2\,\,V-1s-1 , and 1.21× 104 , respectively. After applying pressure under accumulation mode operation, the drain current ( I_D) of the device reduces and the OFF-current factor increases. Besides, the V_ th of the device shifts toward higher positive gate voltage when external pressure has varied from 0.8 mbar to 1.6 bar. The drain current reduction, enhancement of OFF-current factor, and V_ th shifting during the application of pressure of 1.6 bar are 50%, 300%, and 2000%, respectively, with respect to their normal operation. The variation of all these parameters has two distinct regions with good linearity, one is < 80 mbar and the other is > 80 mbar, which is due to the saturation of orientation of the electric dipole of PVDF-HFP under a certain pressure range (< 80 mbar). Moreover, device response and recovery time are 90 and 5 ms, respectively, indicating its prompt response to external pressure. © 2001-2012 IEEE.